1,8‐Dihydroxynaphthalene (DHN) melanin provides unequal protection to black fungi Knufia petricola and Cryomyces antarcticus from UV‐B radiation - Catanzaro, Ilaria; Gorbushina, Anna A.; Onofri, Silvano; Schumacher, Julia (Environmental Microbiology Reports, 2024)
Black fungi on rock surfaces endure a spectrum of abiotic stresses, including UV radiation. Their ability to tolerate extreme conditions is attributed to the convergent evolution of adaptive traits, primarily highly melanized cell walls. However, studies on fungal melanins have not provided univocal results on their photoprotective functions. Here, we investigated whether the black fungi Knufia petricola and Cryomyces antarcticus only use DHN melanin or may employ alternative mechanisms to counteract UV‐induced damage. For this, melanized wild types and non‐melanized Δpks1 mutants were exposed to different doses of UV‐B (312 nm) followed by incubation in constant darkness or in light–dark cycles to allow light‐dependent DNA repair by photolyases (photoreactivation). C. antarcticus could tolerate higher UV‐B doses but was sensitive to white light, whereas K. petricola showed the opposite trend. DHN melanin provided UV‐B protection in C. antarcticus, whereas the same pigment or even carotenoids proved ineffective in K. petricola. Both fungi demonstrated functional photoreactivation in agreement with the presence of photolyase‐encoding genes. Our findings reveal that although the adaptive trait of DHN melanization commonly occurs across black fungi, it is not equally functional and that there are species‐specific adaptations towards either UV‐induced lesion avoidance or repair strategies.